Risk assessment of staphylococcal poisoning due to consumption of informally-marketed milk and home-made yoghurt in Debre Zeit, Ethiopia - Makita, K.; Desissa, F.; Teklu, A.; Zewde, G.; Grace, Delia (Elsevier, 2012)
The objectives of the study were twofold: to prove that participatory risk assessment can be applied to informally-marketed foods, and to assess the risk of staphylococcal poisoning through consumption of raw milk and home-made yoghurt in Debre Zeit, Ethiopia. Rapid urban appraisals were combined with conventional interviews to identify and quantify formal and informal milk value chains and to collect information on consumers’ food preparation and consumption behavior. Milk was sampled in 170 dairy farms and 5 milk collection centres and microbiological tests were conducted. Published data on milk fermentation in Ethiopia was combined with a growth model of Staphylococcus aureus to develop a stochastic risk model. The annual incidence rate of staphylococcal poisoning was estimated to be 20.0 (90% CI: 13.9-26.9) per 1,000 people. When the effect of fermentation was removed from the model, the annual incidence rate increased to 315.8 (90% CI: 224.3-422.9) per 1,000 people, showing the importance of traditional food preparation methods in risk mitigation; traditional milk fermentation reduced the risk by 93.7%. Improving the safety of milk and dairy products could be achieved through supporting appropriate traditional food preparation and consumption where an industrial risk mitigation system is not feasible. Participatory risk assessment was shown to be applicable to informal food value chain.